Menanamkan Nilai-Nilai Keorganisasian Bagi Siswa SMKN 4 Kota Bengkulu Dalam Pembangunan Pendidikan - Saputra, Harius Eko; Rikardo, Yanuar; Sariningsih, Marida; Sumantri, Muhammad Oky; Purnama, Bimas Endo (LPPJPHKI Universitas Dehasen Bengkulu, 2022)
This community service activity aims to instill organizational values in students of SMKN 4 Bengkulu City as an effort to strengthen educational development. School-based organizations play a vital role in shaping students' character, enhancing soft and hard skills, and cultivating leadership and social responsibility. The program was implemented through face-to-face counseling using a participatory approach, involving students actively in discussions and organizational training. The results of the activity indicate an improvement in students' understanding of organizational meaning, time management skills, and awareness of the importance of active participation in school organizations. Furthermore, students demonstrated greater motivation to develop creativity and innovation in organizational activities. Support from the school and enthusiasm from the participants were key factors in the success of this initiative. This program contributes to forming a young generation ready to actively participate in sustainable educational development. The findings suggest the need for replication in other schools and policy reinforcement to support systematic student organization development.